+0  
 
0
134
1
avatar+3636 

Help 15

NotSoSmart  Mar 5, 2018
 #1
avatar+68 
+2

15)

\(\frac{\frac{n-4}{n^2-2n-15}}{\frac{n+1}{n+3}}\)

Simplify the polynomial.

\(\frac{\frac{n-4}{(n-5)(n+3)}}{\frac{n+1}{n+3}}\)

Multiply the top and the bottom fraction by the common equation, which is \((n-5)(n+3)\) .

\(\frac{n-4}{(n-5)(n+1)}\)

Choice 3

-----------------

16)

Take all the bottom numbers and make them equal to 0.

\(a^2-16=0, a-4=0, a+4=0\)

\(a^2=16, a=4, a=-4\)

\(a=4, a=4, a=-4\)

So that means \(a\) can NOT be 4 or -4.

Choose the option without those 2 numbers.

Choice 4.

CoopTheDupe  Mar 5, 2018

24 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.